2020
DOI: 10.1037/str0000119
|View full text |Cite
|
Sign up to set email alerts
|

Baseline psychosocial and affective context characteristics predict outcome expectancy as a process appraisal of an organizational health intervention.

Abstract: This study aims to examine how far group-level psychosocial and affective factors, as a relevant context, predict outcome expectancy as a process appraisal of an organizational health intervention. For this purpose, data from a university hospital (N = 250 representatives from 29 nursing wards) were collected. Participants took part in an intervention consisting of four-day workshops designed to improve psychosocial working conditions. Employee surveys covered baseline psychosocial (job demands and job resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 83 publications
(137 reference statements)
1
5
0
Order By: Relevance
“…These task characteristics thus also have the power to protect nurses from experiencing the most detrimental (from an outcome perspective) affective experiences at work. When considered together, these results are consistent with prior results supporting the benefits of job resources in relation to nurses’ affective states (Lehmann et al, 2020). These results also generally support the beneficial role of job resources emphasized by the JD-R theory (Bakker & Demerouti, 2017) and encourage managers to nurture and support job resources within health care organizations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These task characteristics thus also have the power to protect nurses from experiencing the most detrimental (from an outcome perspective) affective experiences at work. When considered together, these results are consistent with prior results supporting the benefits of job resources in relation to nurses’ affective states (Lehmann et al, 2020). These results also generally support the beneficial role of job resources emphasized by the JD-R theory (Bakker & Demerouti, 2017) and encourage managers to nurture and support job resources within health care organizations.…”
Section: Discussionsupporting
confidence: 90%
“…Supporting our expectations, our results revealed five profiles of nurses characterized by distinctive configurations of affective states: (1) intense mixed emotions incapacitators ; (2) mixed emotions incapacitators ; (3) high negative affect incapacitators ; (4) normative ; and (5) low negative affect facilitators. Moreover, in their previous study of nurses, Lehmann et al (2020) showed that the valence of affect intensity (i.e., positive vs. negative) was the only significant predictor of efficacy beliefs (i.e., affect direction), suggesting that affect direction is not a matter of activation but rather a matter of valence. In line with this suggestion, two profiles identified in this study ( normative and low negative affect facilitators ) were consistent with those identified by Sandrin et al (2020), suggesting that these profiles might be independent of the activated nature of affective states.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On may also refer to the organizational climate literature (e.g., Bronkhorst et al, 2015) that further highlights the importance of leadership and supervision. For OHIs in particular, it has been shown that supportive leadership as a contextual variable is associated with the intervention process (Lehmann et al, 2018). Moreover, it would be interesting to examine whether the intervention context (in this case team climate) changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of this estimate, idea or prediction is influenced by the previous positive or negative outcome. That is, after a positive outcome, expectations of success will increase and vice versa (Lehmann et al, 2020;Zheng et al, 2018). Previous studies affirm that performance expectancy is a factor of great importance in predicting the intention to use a system or technology.…”
Section: Proposed Model and Justification Of Hypothesesmentioning
confidence: 99%